Gestión administrativa y su incidencia en la producción de la empresa agrícola bananera “Princesa Bananas” parroquia La Unión cantón Valencia, año 2013 - Lino Tigua, Sindy Jessenia (2015)
The research project was based on an analysis of the Administrative Management and its impact on agricultural production company Princess Bananas, Canton Valencia. Given that the main problem is the inadequate level of production in the company which affects the performance of the administration planned is why has identified the following objectives in this research work such as: Studying the administrative process and its relation to the production system of the company, examine the achievements of the administration and influence the level of production of the Banana Company and finally design a plan of administration that allows the contribution to increased production level and correct certain shortcomings detected with the detailed study of each area examined. The purpose of this thesis make the Princess Banana Bananas Agricultural Company is to minimize the deficiencies that have both the administration and the production process for the proper functioning and efficiency of human talent with the desire to achieve the desired goals, increase production and get a better administration. The development of this project began with the implementation of interviews and surveys to staff working in the company, both in administration and in the production area, which served to have a starting point and determine whether the Administrative Management the company falls significantly in the area of production thereof. Finally the respective conclusions and recommendations of the research are described, which are based on the results and finally Administrative Management plan that allows the contribution to increased agricultural production company Princess Banana Bananas is performed.